2000
DOI: 10.1007/bf02253362
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes of superoxide dismutase and catalase activities in the rat brain

Abstract: Oxygen free radicals have been proposed to be involved in the process of aging. Superoxide dismutase (SOD) and catalase are important for antioxidative defense. In this study, profiles of SOD, catalase, and their mRNA levels were investigated in the frontal, parietal, temporal and occipital lobes, subcortex and cerebellum of male Wistar rats at ages 1-21 months. The total SOD and Mn SOD activities increased with age and exhibited higher levels at 6 and 12 months but decreased thereafter. Activity of catalase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 30 publications
6
29
1
Order By: Relevance
“…SOD activity is increased with age until 12 months and decreased after 12 months in the rat brain (Tsay et al 2000). Cell culture study (Chan et al 2009) and our results are consistent in this regard revealing that treatment with astaxanthin restores the activity of CAT.…”
Section: Discussionsupporting
confidence: 93%
“…SOD activity is increased with age until 12 months and decreased after 12 months in the rat brain (Tsay et al 2000). Cell culture study (Chan et al 2009) and our results are consistent in this regard revealing that treatment with astaxanthin restores the activity of CAT.…”
Section: Discussionsupporting
confidence: 93%
“…The burden of ROS during aging may induce protein oxidation and result in the disruptions of the antioxidant enzymes in the brain, which are responsible for the scavenger of free radicals. Previous studies revealed that antioxidant enzyme activities (SOD1, SOD2, catalase, and glutathione peroxidase) showed age-related decrease in the brain, indicating that the antioxidant defense declined during aging and neurodegenerative diseases [8,9,11,31]. In our results, SOD1, SOD2, Prdx1, and PPIA were oxidized in the aged rat temporal cortex.…”
Section: Discussioncontrasting
confidence: 40%
“…However, the activities of many pivotal antioxidant enzymes (SOD1, SOD2, catalase, and glutathione peroxidase) decrease in the aged rat [8][9][10][11]. Furthermore, the intracellular glutathione concentration was found to decrease with age in the brain [12,13].…”
Section: Introductionmentioning
confidence: 92%
“…There are a large number of mitochondria in the human cerebellar Purkinje cell layer [36], with the number estimated to be even greater than that in the frontal or temporal cortices and putamen [37]. In addition, in rats, the cerebellum demonstrates the lowest levels in any brain region of magnesium superoxide dismutase, the antioxidant enzyme [38].…”
Section: Discussionmentioning
confidence: 99%